2021
DOI: 10.1093/gbe/evab152
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of recombination landscapes in diverging populations of bread wheat

Abstract: Reciprocal exchanges of DNA (crossovers) that occur during meiosis are mandatory to ensure the production of fertile gametes in sexually reproducing species. They also contribute to shuffle parental alleles into new combinations thereby fuelling genetic variation and evolution. However, due to biological constraints, the recombination landscape is highly heterogeneous along the genome which limits the range of allelic combinations and the adaptability of populations. An approach to better understand the constr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 97 publications
(158 reference statements)
1
18
0
Order By: Relevance
“…The wheat population was genotyped on two different single nucleotide polymorphism(SNP) arrays, the Breedwheat Affymetrix Axiom 410K array [ 50 , 51 ] and the Illumina Infinium iSelect Wheat 90K array [ 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…The wheat population was genotyped on two different single nucleotide polymorphism(SNP) arrays, the Breedwheat Affymetrix Axiom 410K array [ 50 , 51 ] and the Illumina Infinium iSelect Wheat 90K array [ 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…domestication events) would cause lower effective recombination rates caused by a reduction in the effective population size ( Ne ) (Torres et al 2020; Beissinger et al 2016). On the other hand, broad-scale LD-based estimates were shown to correlate well with per-generation meiotic recombination rates (cM/Mb) in plants estimated based on linkage maps (Choi et al 2013; Dreissig et al 2019; Marand et al 2019; Danguy des Déserts et al 2021; Fuentes et al 2021). Based on this, we focused on weedy and wild populations that did not undergo recent demographic changes such as domestication bottlenecks (Sun et al 2021; Badr et al 2000; Kilian et al 2006; Russell et al 2016).…”
Section: Resultsmentioning
confidence: 95%
“…Based on this, we focused on weedy and wild populations that did not undergo recent demographic changes such as domestication bottlenecks (Sun et al 2021; Badr et al 2000; Kilian et al 2006; Russell et al 2016). Recombination landscapes were shown to vary within and between plant and animal species, with rank correlations ranging from 0.4 to > 0.9 between populations within species (Bauer et al 2013; Dreissig et al 2019; Spence & Song 2019; Schreiber et al 2022; Danguy des Déserts et al 2021). In previous work, we characterized intraspecific recombination landscape variation among populations of rye, and found that the fraction of low-recombining regions varied from 24.2 % to 42.1 % between weedy and domesticated rye (Schreiber et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the high density of SNPs allowed us to observe a significant association of COs with genic features as well as a higher frequency of a DNA motif specific to the TIR-Mariner DNA transposon in recombinant intervals. A similar approach was adopted using the same SNP array to genotype 371 landraces representing four diverging populations (West Asia, East Asia, West Europe, and East Europe) [ 39 ]. Recombination landscapes of the four populations positively correlated between each other and significantly shared most recombinogenic intervals.…”
Section: A Genomics Toolbox For Wheat Research and Breedingmentioning
confidence: 99%